GAMIFICATION APPROACH IN DIGITAL LEARNING ENVIRONMENTS TOWARDS STUDENT EXPERIENCE AND ENGAGEMENT - Rahma Djati Kusuma; Wahyu Indra Satria; Febri Damatraseta (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study explores the integration of gamification in digital learning environments, specifically within Learning Management Systems (LMS), to enhance student motivation and engagement. Despite the rapid advancement of technology in higher education, challenges such as low student engagement and lack of motivation persist. Previous research, including Zea Ulhaque, Fachrezi, and Hadiapurwa (2024), has highlighted that traditional, one-way instructional methods often fail to actively engage students, impacting academic performance. In response, gamification has emerged as a promising solution, with studies indicating that incorporating game elements like points, badges, leaderboards, and challenges can significantly boost student participation and motivation. The research employs a qualitative approach, utilizing a literature review method to synthesize existing studies on the effects of gamification on student learning outcomes. By reviewing the integration of gamified elements in LMS platforms, this study aims to offer a comprehensive understanding of their impact on student engagement and motivation. The findings suggest that gamification not only increases student interaction with learning materials but also fosters a more dynamic and enjoyable learning experience. The study concludes by recommending that educational institutions consider incorporating gamification into their LMS to improve student engagement and learning outcomes, with further research needed to explore its long-term effects and challenges in different educational contexts.